Research on the Construction and Application of Chinese Enterprises Overseas Port Investment Confidence Index Based on D-S Evidence Theory - Chen, Bingji; Jia, Zilong; Liu, Yang (International Journal of Business, Economics and Management, 2020)
After the "One Belt, One Road" strategy was proposed, China's overseas port investment has developed rapidly. In order to help Chinese port companies reduce their investment risks, this article provides help and suggestions for Chinese companies’ overseas port investments by establishing a port investment confidence index system. This article has established a port investment confidence index system, covering four aspects: economic scale, external links, internal vitality and institutional quality. Then, through DS evidence theory, using the subjective weights obtained from the questionnaire survey and the objective weights calculated from the data obtained from each database query to evaluate some countries along the “Belt and Road” route to prove the rationality and operability of the indicator system designed in this article And provide advice and assistance for Chinese companies’ overseas port investment. Based on the subjective weights obtained in this article, Chinese companies are more inclined to invest in economies with better internal economic development and a sound institutional environment. By comparing the objective weights of income, this paper finds that when companies invest in economies with a higher degree of development, they pay more attention to the impact of the business environment of the economy when they invest in economies with a higher degree of development. Low-level economies will give priority to the profitability and development prospects of ports when investing.